Environmental science : - Enger, Eldon D. (McGraw-Hill, 2000)
This book is organized to provide an even, logical flow of concepts and to provide clear illustrations of the major environmental issues of today as interrelatedness; ecological principles and their application; energy; human influences on ecosystems; and pollution and policy